Effect of process parameters on friction stir lap welded 304 stainless steel and 5052 aluminium alloys - Chitturi, V. (American Society of Mechanical Engineers (ASME), 2020)
Joining of two different materials like aluminium and steelis a challenging task because of the vast differences in theirphysical, mechanical and chemical properties. Friction stirwelding is a solid-state joining technique which is successful injoining dissimilar materials. In this study, the tool made withTungsten-Rhenium with a pin length of 4.1 mm is used to weld4 mm stainless steel and 2 mm aluminium plates in lapconfiguration with steel as the top plate. The processparameters used in the study are tool rotational speeds between800 rpm and 1200 rpm, traverse speed ranging from 20 mm/minto 40 mm/min, penetration depth of 4.1 mm to 4.3 mm with avarying tilt between from 0° and 2.5°. The Aluminium is meltedduring the process because of the high temperature and isthrown out in the form of flash resulting in the formation ofdefects and a cup like structure at the weld zone.Microstructural analysis confirmed that formation of a soundjoint without defects was impossible. The mechanically stirredzone consists of a thin intermetallic layer at the interface ofaluminium and steel plates. The thickness of the intermetalliclayers formed were between 5 °m and 20 °m. The maximumshear strength of 2.7 kN was achieved with tool rotational speedof 1000 rpm, penetration depth of 4.3 mm and welding speed of30 mm/min when the angle was tilted at 0°. It is evident fromthe experiments that the joints achieved were not defect freebecause of improper mixing of the material. © 2020 American Society of Mechanical Engineers (ASME). All rights reserved.